Does family come first? Family motivation-individual's OCB assessment via self-efficacy. Issue 6 (18th December 2019) - Umrani, Waheed Ali; Siyal, Imdad Ali; Ahmed, Umair; Ali Arain, Ghulam; Sayed, Hassan; Umrani, Sumera
Abstract : Purpose: The purpose of this paper is to investigate the perceptions of faculty members about the influence of family motivation on their self-efficacy and organizational citizenship behavior-individual (OCBI). Design/methodology/approach: The proposed model was tested on a sample of 353 faculty members from different public and private universities of Pakistan. Partial least squares structural equation modeling was used to analyze data. Findings: Surprisingly, results reveal that family motivation was not positively related to faculty members' OCBI; instead, this relationship is fully mediated by self-efficacy. The findings suggest that it is employees' self-efficacy belief through which their family motivation translates to their increased OCBI. This study also finds that supporting the family is a powerful source of motivation to work, offering meaningful practical and theoretical implications for policy-makers, leaders, managers and researchers on the new dynamics of work and family engagements. Originality/value: The study contributes to human resource management (HRM) and organizational behavior (OB) literatures by providing some useful practical implications for managers and HRM and OB consultants who are interested in understanding the underlying psychological mechanisms (i.e. self-efficacy) through which employees' family motivation results in the increased OCBI.